Vectorial directions of the teaching activity in the period of Second Academical Revolution - Terentieva, Nataliia (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The paper presents the main trends associated with so-called human factor inherent in higher education during the Second Academic Revolution. Been defined and characterized the changing lecture role, the specific teaching of this period. Author presents the positive and negative aspects of teaching, including the diversification and specialization of activity due to changes in student population, reducing the quality of the learning and teaching activities, migration, increased responsibility and accountability of teachers, etc.
Keywords: trends in higher education; the Second Academic Revolution; massification; diversification; segmentation; interdisciplinary thinking